How Will We Ever Resolve the Library Digital Content Problem? - Inouye, Alan (Maine Policy Review, 2024)
Library access to digital content is characterized by a big dose of exasperation. Although digital content provides some remarkable benefits, the shift of the access rubric from copyright to licenses provided many inferior provisions for libraries. This dilemma spans library type, and features the digital book issue with public libraries in the 2010s to the present. In the past decades, the library community has advocated for change via direct engagement with the industry, state legislation, federal policy and media campaigns. Overall, these efforts have been modestly effective at best. Fundamental reconsideration of the path forward is needed. The first step on that path is a thoughtful assessment of the needs and opportunities for digital content in libraries, and the resulting possible policy directions.